ANALISIS GAYA BELAJAR SISWA KELAS V PADA PEMBELAJARAN TEMATIK TEMA 1 SUBTEMA 1 SD NEGERI KALIKALONG 01 PATI - Ummi Rosidah; Mudzanatun; Duwi Nuvitalia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
There are still many students who are not aware of their respective learning styles so that the management process in the classroom is not maximized. Teachers also do not know what approach should be made to students with different learning styles. The research objective was to determine the learning styles of each fifth grade student at SD Negeri Kalikalong 01. The research method used was a qualitative method. The qualitative method is a method used to search for data in depth and find its meaning. The population in this study were 21 students in class V SD Negeri Kalikalong 01 Pati. The data in this study were obtained through questionnaires, interviews, and observations on thematic learning theme 1 sub-theme 1. The results showed that the learning styles of students in class V were dominated by students visual type with a percentage of 48%, auditory type learners with a percentage of 38%, kinesthetic type learners 14%. The teacher's learning approach can be adapted to the different learning styles of students. For the visual learning style, the approach is to display subject matter combined with images and displayed on a projector, for the auditory learning style, an approach can be made by asking more oral questions, for the kinesthetic learning style, an approach is carried out that makes students move a lot, such as learning by looking at nature around or held practice activities.